Reflection of Feminist thought on Contemporary Painting in the Iraqi Kurdistan Region - ابراهیم, ‌‌ا.د. بیان; ازاد, م. شانو (Sulaimani Journal for Humanities, 2025)
Feminism is a women's movement that attempts to defend women's rights in the areas of sexism, structural and economic inequality, power, oppression, gender roles and stereotypes. It also studies women's issues as a thought, and it is clear that the field of art as a mirror of society, quickly adopted this theory, this art was given a different importance in contemporary art, because it paid more attention to new media such as performance. The body is video and installation art, and this reflection of feminism on contemporary art in the world raises a serious question for the researcher: What is the impact and reflection of feminist thought in the Kurdistan Region on contemporary art in the Kurdistan Region? To answer this question, the researcher conducted research entitled (Reflection of Feminist Thought in Contemporary plastic art in the Kurdistan Region of Iraq) which consists of four parts and the theoretical framework consists of four studies. The research method is the descriptive method of analysis. This study aims to present the reflection of feminist thought on contemporary plastic art in the Kurdistan Region of Iraq, within the limits of the scope of the study. The limits of the topic are the reflection of feminist thought on contemporary plastic art. The locational limit is the Iraqi Kurdistan region, and the time limit is the period between 2010-2022. Then the research community includes the artworks of artists from the Iraqi Kurdistan region during the period of contemporary art between 2010-2022, then analyzing three examples, with the aim of Explaining the level of reflection of this feminist thought on contemporary plastic art in the region, and in the fourth section, the results of the study are mentioned.
Keywords: Feminist thought; Contemporary art; Feminist art